Comparative transcriptome-wide identification and differential expression of genes and lncRNAs in rice near-isogenic line (KW-Bph36-NIL) in response to BPH feeding - Xue, Yanxia; Muhammad, Sajid; Yang, Jinlian; Wang, Xuan; Zhao, Neng; Qin, Baoxiang; Qiu, Yongfu; Du, Zhimin; Ulhassan, Zaid; Zhou, Weijun; Liu, Fang; Li, Rongbai (Frontiers in Plant Science, 2023)
Brown planthopper (BPH) is the most devastating pest of rice in Asia, causing substantial yield losses and has become a challenging task to be controlled under field conditions. Although extensive measures have been taken over the past decades which resulted in the evolution of new resistant BPH strains. Therefore, besides other possible approaches, equipping host plants with resistant genes is the most effective and environment-friendly technique for BPH control. Here, we systematically analyzed transcriptome changes in the susceptible rice variety Kangwenqingzhan (KW) and the resistant near-isogenic line (NIL) KW-Bph36-NIL, through RNA-seq, depicting the differential expression profiles of mRNAs and long non-coding RNAs (lncRNAs) in rice before and after BPH feeding. We observed a proportion of genes (1.48%) and (2.74%) were altered in KW and NIL, respectively, indicating different responses of rice strains against BPH feeding. Nevertheless, we characterized 384 Differentially Expressed long non-coding RNAs (DELs) that can be impacted by the two strains by alternatively changing the expression patterns of the respective coding genes, suggesting their certain involvement in response to BPH feeding. In BPH invasion, KW and NIL responded differently by modifying the synthesis, storage, and transformation of intracellular substances, adjusting the nutrient accumulation and utilization inside and outside the cells. In addition, NIL expressed stronger resistance by acutely up-regulating genes and other transcription factors related to stress resistance and plant immunity. Altogether, our study elaborates valuable insights into the genome-wide DEGs and DELs expression profiles of rice under BPH invasion by high throughput sequencing and further suggests that NILs can be utilized in BPH resistance breeding programs in developing high-resistance rice lines.